RFID enabled mugs for customer loyalty application - Paulino, Iris Judith M. (2011)
Radio Frequency Identification (RFID) is the use of radio waves for tracking and pulling information from an object where an RFID tag is applied or incorporated to it. Today, they are being used for timing marathons, triathlon, cycling, etc; enhancing inventory control, tracking patients in hospitals and a lot more. For this project, an application for RFID in coffee shop would be introduced. RFID is used to identify a customer's name, previous purchases and usual orders, account load or balance, and other information such as birthday, etc. This helps in making service faster and easier because there would ease of remembering what customers usually order in the store and payment may be post-paid or pre-paid. Furthermore, this helps in gaining customer loyalty and giving away discounts. For this project, the RFID tag is attached to a silicone mug sleeve that is used to keep hands from burning when holding the mug. The tag is then captured by the RFID reader that is placed either on the counter or the drive-thru section of the coffee shop. Data on the tag is then stored to the shop's database. A program for the reader to capture the tag without collisions is made. Afterwards, more tests and set-ups are done to guide the users of the effects of washing the mugs manually and placing it in a microwave and heated dishwasher.